The Influence of Learning Methods and Learning Motivation on Discs Throwing Skills (Experimental Study at SMP Negeri 24 Makassar - Suriah Hanafi; Moch Asmawi; Firmansyah Dlis (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
Aimfrom this research is to see the differences in three forms of learning methods, namely, the overall learning method, part learning method and mixed learning methods on the discus throwing skills of class IX students of SMP Negeri 24 Makassar who are members of the extra-curricular. The moderator variable in this study is learning motivation. The dependent variable is the discus throwing skill. This study used a 2x3 factorial experimental method, the population of this study was 134 students of SMP Negeri 24 Makassar. The determination of the sample size was based on purposive sampling technique by selecting 27% of the total data with the highest score and 27% of the lowest score referring to the Verducci theory. The conclusion from this research is that the group of students who are taught using the overall learning method has better results in discus throwing skills compared to the group of students who are taught disc-throwing skills using the part learning method and groups of students who are taught with mixed learning methods. For students who have high motivation, the learning method using the overall method is better used in teaching disc-throwing skills, for students with low motivation categories the mixed learning method is better used in teaching disc throwing skills than using the whole learning method and the part learning method in improving disc throwing skills